High-temperature-resistant low-smoke halogen-free flame-retardant twisted-pair cable for building security system and preparation method thereof

Through the combination technology of modified magnesium hydroxide and alkaline lignin, high-temperature, low-smoke, halogen-free flame-retardant twisted pair cables were prepared, which solved the problems of flammability and smoke generation in traditional cables in fires, and achieved more High flame retardant performance and safety.

CN119274890AActive Publication Date: 2025-01-07ZHEJIANG TIANJIE IND

Patent Information

Application Number
CN202411823648.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-07
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

Traditional cables are prone to ignition in fires, releasing toxic gases and large amounts of smoke, affecting evacuation and rescue, and have insufficient heat resistance, which cannot effectively suppress the spread of fire.

Method used

Modified magnesium hydroxide was prepared by sol-gel method, and a silica coating was introduced on its surface, combining the phosphorus-nitrogen structure of alkaline lignin and the catalytic carbonization reaction to form high temperature, low smoke and halogen resistance without resistance Burning twisted pair cable.

Benefits of technology

Significantly reduce the surface temperature of the material, form a dense protective layer and carbon layer, interrupt the combustion chain reaction, reduce smoke generation, and improve flame retardant performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119274890A_ABST
    Figure CN119274890A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of cables, and provides a high-temperature-resistant low-smoke halogen-free flame-retardant twisted-pair cable for a building security system and a preparation method thereof. Magnesium hydroxide is modified by adopting a sol-gel method, and the surface of the magnesium hydroxide is coated with silicon dioxide, so that the magnesium hydroxide has excellent hydration effect and free radical capture capability at high temperature, and the flame retardance and smoke suppression performance are improved; secondly, on the basis of alkaline lignin, through chemical modification of phosphonitrilic chloride trimer and triphenyl phosphate, a phosphorus-nitrogen structure and a phosphate group are introduced, the thermal stability and carbonization capacity of lignin are remarkably enhanced under the catalytic action of titanium dioxide, and a compact carbonization protection layer is formed to block oxygen and heat. The two flame-retardant materials are respectively fused and mixed to finally obtain the low-smoke halogen-free flame-retardant cable. The cable material has excellent flame retardance and low smoke emission performance, and is suitable for building security and protection systems with high safety requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cables and relates to a high-temperature resistant, low-smoke, halogen-free and flame-retardant twisted-pair cable for a building security system and a preparation method thereof. Background Art

[0002] Modern building security systems undertake the important task of ensuring building safety and personal and property safety. However, the performance of traditional cables under extreme conditions such as fire may have many hidden dangers: traditional cables are easy to support combustion in fires, release a lot of heat and accelerate the spread of fire; the halogen materials used in traditional cables will produce toxic gases when burning, which is harmful to human health; during the combustion process, a lot of smoke is released, affecting evacuation and rescue. Therefore, it is necessary to prepare a high-temperature resistant, low-smoke, halogen-free, flame-retardant twisted-pair cable for building security systems. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-temperature resistant, low-smoke, halogen-free, flame-retardant twisted-pair cable for a building security system and a preparation method thereof. Modified magnesium hydroxide is prepared by a sol-gel method, and a silicon dioxide coating layer is introduced on its surface to enhance the flame retardant and smoke suppression properties; at the same time, alkaline lignin is used as a raw material, modified by hexachlorocyclotriphosphazene and triphenyl phosphate, a phosphorus-nitrogen structure and a phosphate group are introduced, and titanium dioxide is used to catalyze the carbonization reaction to enhance the heat resistance and carbonization ability of lignin, thereby meeting the needs of actual production.

[0004] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system, the preparation method comprising: Step S1, under N2 atmosphere, 2,5-dihydroxybenzoic acid is dispersed in dimethyl sulfoxide and mixed evenly, then N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide are added, and stirring is continued at a first stirring speed, and the temperature is raised to a first temperature for sufficient reaction, and after the reaction is completed, washing and distillation are performed to obtain product A; Step S2, adding Mg(OH)2 and an emulsifier to an ethanol aqueous solution, heating to a second temperature, adding a sodium hydroxide solution to adjust the pH to 10, adding tetraethyl orthosilicate, and fully reacting at the second temperature, washing and filtering after the reaction is completed, and vacuum drying at a third temperature to obtain modified Mg(OH)2; Step S3, dispersing modified Mg(OH)2 and triethylamine in dimethyl sulfoxide, heating to the second temperature, adding product A to fully react, cooling to room temperature after the reaction, washing with anhydrous ethanol, and fully drying at a fourth temperature to obtain a Mg(OH)2 flame retardant; Step S4, under N2 atmosphere, dissolving alkaline lignin in N,N-dimethylformamide, stirring continuously at a second stirring speed, adding pyridine and continuing stirring to obtain a mixed solution, dispersing hexachlorocyclotriphosphazene and triphenyl phosphate in N,N-dimethylformamide respectively, adding the dispersed mixture to the mixed solution, adding metaphosphoric acid, melamine cyanurate and titanium dioxide, heating to a fourth temperature, stirring continuously at the second stirring speed to react, filtering and washing after the reaction, and placing at a fifth temperature to fully dry to obtain flame retardant lignin; Step S5, mixing Mg(OH)2 flame retardant, ethylene-vinyl acetate copolymer, vinyl silane and zinc stearate in proportion, putting them into a twin-screw extruder, and melt mixing them at a sixth temperature to obtain an insulating layer material; putting flame-retardant lignin, low-density polyethylene, antioxidant 1010, UV-329 and zinc stearate into a second twin-screw extruder, and melt mixing them at a seventh temperature to obtain a sheath layer material, and uniformly coating the insulating layer material and the sheath layer material on the surface of the battery core in turn, and then mechanically twisting the two coated cables to obtain a high temperature resistant, low smoke, halogen-free, flame-retardant twisted pair cable for a building security system.

[0005] 2,5-dihydroxybenzoic acid contains a carboxyl group and a benzene ring. The carboxyl group itself is a relatively stable functional group with low reactivity. N,N'-dicyclohexylcarbodiimide reacts with the carboxyl group of carboxylic acid to form a carboxylic acid acyl intermediate and releases dicyclohexylurea. This carboxylic acid acyl intermediate is more active than the original carboxyl group and is easy to react with other reactants. N-hydroxysuccinimide can form an N-hydroxysuccinimide ester with the generated carboxylic acid acyl intermediate, which enhances its reactivity and can react nucleophilically with other compounds containing nucleophilic groups. At the same time, 2,5-dihydroxybenzoic acid and its derivatives contain phenolic hydroxyl structures. Phenolic hydroxyl groups have strong reducing properties and can neutralize free radicals by providing electrons. Free radicals are generated during fire and promote combustion reactions. By reacting with these free radicals, the phenolic hydroxyl groups of 2,5-dihydroxybenzoic acid can effectively inhibit oxidation reactions and form stable phenol free radicals, thereby breaking the chain reaction of free radicals. This not only reduces the occurrence of oxidation reactions, but also reduces the release of harmful gases during pyrolysis, reduces the generation of smoke, slows down the thermal degradation process of materials, and reduces the combustion rate in fires. In addition, under high temperature conditions, compounds containing phenolic hydroxyl groups can interact with the matrix material through hydrogen bonds, π-π stacking, etc. to form a more stable polymer network. Phenolic hydroxyl is a group with a hydrogen bond donor and has a strong electron affinity. Phenolic hydroxyl molecules can form hydrogen bonds and interact with the molecular chains of other materials through such hydrogen bonds, thereby enhancing the structure and performance of the material; 2,5-dihydroxybenzoic acid has an aromatic ring structure. Due to the presence of its electron cloud, the aromatic ring has a strong π-π stacking ability, that is, the benzene rings can attract each other through π-π interactions to form a relatively stable structure, thereby limiting the movement of the molecular chain at high temperatures and enhancing the heat resistance of the material.

[0006] The hydration effect is one of the key mechanisms for magnesium hydroxide to play a flame retardant role under high temperature conditions. The structure of Mg(OH)2 contains abundant hydroxyl groups. During the heating process, the water molecules released when Mg(OH)2 decompose form hydrates on the surface of magnesium oxide, which increases the thermal stability of the surface. When the heat of the fire source is transferred to magnesium oxide, these hydrates are gradually released, providing a continuous cooling effect. This process can not only reduce the temperature of the fire source, but also inhibit the oxidation reaction at high temperature through evaporative cooling. The hydroxyl groups on the surface of Mg(OH)2 can interact with the emulsifier to modify the hydrophilicity of the surface of magnesium hydroxide and improve its compatibility with other materials. Hexadecyltrimethylammonium bromide has hydrophilic amino groups and lipophilic alkyl chains in the solution, which can be adsorbed on the surface of magnesium hydroxide to help improve the dispersibility of Mg(OH)2. At the same time, hexadecyltrimethylammonium bromide can reduce the mutual attraction between magnesium hydroxide particles by forming a charge shielding layer and hydrophobic interaction, thereby preventing the agglomeration of particles and ensuring that they are evenly dispersed in the solution. Tetraethyl orthosilicate is hydrolyzed under alkaline conditions to form silanol groups, which further react with the hydroxyl groups on the surface of magnesium hydroxide. The Si-O-Mg bond formed is very stable, which can form a silicate layer on the surface of Mg(OH)2, further improving the thermal stability and fire resistance of Mg(OH)2. In addition, tetraethyl orthosilicate can further react with itself to form silicon-oxygen chains, forming a three-dimensional silicon-oxygen network structure on the surface of Mg(OH)2, thereby improving the thermal stability of magnesium hydroxide.

[0007] The surface of modified Mg(OH)2 carries siloxy groups, which can react with hydroxyl or phenolic hydroxyl in product A to form Mg-O-Si bond or Si-O-Si bond. Triethylamine, as an alkaline catalyst, promotes the condensation reaction between siloxy groups and hydroxyl groups, so that the modified Mg(OH)2 is further cross-linked in the matrix to form a stable cross-linked network. The cross-linked network limits the thermal motion of the molecular chain at high temperature, thereby slowing down the decomposition rate of the material. At the same time, the cross-linked structure can better withstand high temperature and inhibit heat conduction through enhanced heat shielding effect. The phenolic hydroxyl of product A decomposes at high temperature, captures free radicals in the flame, and reduces the chain propagation of the combustion reaction. Mg(OH)2 decomposes at high temperature to release water vapor, dilute the oxygen concentration and cool the combustion area. The decomposition product (MgO) of Mg(OH)2 will form a heat-insulating protective layer on the surface of the material, which combines with the carbon layer formed by the decomposition of product A to enhance the density and stability of the carbon layer. The aromatic ring promotes the carbonization reaction during the decomposition process, thereby forming a higher quality carbon layer. The combination of the two makes the flame retardant have both physical and chemical flame retardant mechanisms, enhancing the flame retardant effect.

[0008] There are a large number of phenolic hydroxyl groups and carboxyl groups in the lignin structure. Hexachlorocyclotriphosphazene has a three-ring structure. Each phosphorus atom is connected by a nitrogen atom to form a closed ring structure. The chlorine atom on the phosphorus atom is the active center and can undergo a nucleophilic substitution reaction. The phenolic hydroxyl group in lignin is a nucleophilic group that can attack the phosphorus atom in hexachlorocyclotriphosphazene. The chloride ion on the phosphorus atom is replaced to generate a new chemical bond -P=N. The -P=N bond is a polar chemical bond with high chemical stability and thermal stability. The introduction of this structure not only increases the phosphorus content of lignin, but also enhances the heat resistance of the material during combustion. At the same time, it can capture free radicals in the flame and inhibit the combustion chain reaction. Triphenyl phosphate is composed of a phosphate group and three phenol groups. The hydroxyl or phenolic hydroxyl group on the phosphate center has high activity and can undergo esterification reaction with the hydroxyl group of lignin. The phenolic hydroxyl group of lignin acts as a nucleophile to attack the phosphorus atom in triphenyl phosphate. The phenolic group is replaced to form a phosphate bond. The generated phosphate bond has excellent thermal stability at high temperature and can release phosphoric acid and its derivatives during combustion, which can promote the formation of carbon layer at high temperature and prevent the release of combustible gas. The cyanuric acid in melamine cyanurate provides a high nitrogen content. The melamine part has excellent carbon-forming properties, forming a thermally stable nitrogen heterocyclic structure. It decomposes and releases inert gas during combustion, which plays a role in diluting oxygen and cooling. The phosphoric acid product and the nitrogen heterocyclic structure can capture the free radicals generated during the combustion process and inhibit the combustion chain reaction. At the same time, the oxygen vacancies on the TiO2 surface can adsorb the small molecular intermediates generated by the decomposition of lignin, reduce the reaction activation energy of the intermediates, promote their dehydration, decarboxylation or condensation reactions on the surface, and accelerate the carbonization process to form a dense carbon layer.

[0009] As a preferred technical solution of the present invention, in step S1, the mass parts of the 2,5-dihydroxybenzoic acid is 5-10 parts, for example, it can be 5.0 parts, 5.5 parts, 6.0 parts, 6.5 parts, 7.0 parts, 7.5 parts, 8.0 parts, 8.5 parts, 9.0 parts, 9.5 parts or 10.0 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0010] In some optional examples, the mass fraction of dimethyl sulfoxide is 100-120 parts, for example, it can be 100 parts, 102 parts, 104 parts, 106 parts, 108 parts, 110 parts, 112 parts, 114 parts, 116 parts, 118 parts or 120 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0011] In some optional examples, the mass proportion of the N,N'-dicyclohexylcarbodiimide is 7-9 parts, for example, it can be 7.0 parts, 7.2 parts, 7.4 parts, 7.6 parts, 7.8 parts, 8.0 parts, 8.2 parts, 8.4 parts, 8.6 parts, 8.8 parts or 9.0 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0012] In some optional examples, the mass fraction of N-hydroxysuccinimide is 4-6 parts, for example, it can be 4.0 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5.0 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts or 6.0 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] In some optional examples, the first stirring speed is 300-400rpm, for example, it can be 300rpm, 310rpm, 320rpm, 330rpm, 340rpm, 350rpm, 360rpm, 370rpm, 380rpm, 390rpm or 400rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] In some optional examples, the stirring time of the first stirring speed is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] In some optional instances, the first temperature is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] In some optional examples, the reaction time at the first temperature is 4-5h, for example, it can be 4.0h, 4.1h, 4.2h, 4.3h, 4.4h, 4.5h, 4.6h, 4.7h, 4.8h, 4.9h or 5.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] As a preferred technical solution of the present invention, in step S2, the mass proportion of Mg(OH)2 is 80-100 parts, for example, it can be 80 parts, 82 parts, 84 parts, 86 parts, 88 parts, 90 parts, 92 parts, 94 parts, 96 parts, 98 parts or 100 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] In some optional examples, the emulsifier is hexadecyltrimethylammonium bromide, and the weight parts are 2-5 parts, for example, it can be 2.0 parts, 2.3 parts, 2.6 parts, 2.9 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4.1 parts, 4.4 parts, 4.7 parts or 5.0 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] In some optional examples, the mass parts of the ethanol aqueous solution is 400-500 parts, for example, it can be 400 parts, 410 parts, 420 parts, 430 parts, 440 parts, 450 parts, 460 parts, 470 parts, 480 parts, 490 parts or 500 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] In some optional instances, the second temperature is 40-50°C, for example, it can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] In some optional instances, the mass fraction of the sodium hydroxide solution is 10-15wt.%, for example, it can be 10.0wt.%, 10.5wt.%, 11.0wt.%, 11.5wt.%, 12.0wt.%, 12.5wt.%, 13.0wt.%, 13.5wt.%, 14.0wt.%, 14.5wt.% or 15.0wt.%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] In some optional examples, the mass fraction of tetraethyl orthosilicate is 25-35 parts, for example, it can be 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts or 35 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] In some optional examples, the reaction time after adding tetraethyl orthosilicate is 4-5h, for example, it can be 4.0h, 4.1h, 4.2h, 4.3h, 4.4h, 4.5h, 4.6h, 4.7h, 4.8h, 4.9h or 5.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In some optional instances, the third temperature is 100-120°C, for example, it can be 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C or 120°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] In some optional examples, the vacuum drying time at the third temperature is 8-10h, for example, it can be 8.0h, 8.2h, 8.4h, 8.6h, 8.8h, 9.0h, 9.2h, 9.4h, 9.6h, 9.8h or 10.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] As a preferred technical solution of the present invention, in step S3, the mass proportion of the modified Mg(OH)2 is 80-100 parts, for example, it can be 80 parts, 82 parts, 84 parts, 86 parts, 88 parts, 90 parts, 92 parts, 94 parts, 96 parts, 98 parts or 100 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] In some optional examples, the mass fraction of triethylamine is 1-2 parts, for example, it can be 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts or 2.0 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In some optional examples, the mass fraction of dimethyl sulfoxide is 200-220 parts, for example, it can be 200 parts, 202 parts, 204 parts, 206 parts, 208 parts, 210 parts, 212 parts, 214 parts, 216 parts, 218 parts or 220 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In some optional instances, the second temperature is 40-50°C, for example, it can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In some optional examples, the mass proportion of the product A is 5-10 parts, for example, it can be 5.0 parts, 5.5 parts, 6.0 parts, 6.5 parts, 7.0 parts, 7.5 parts, 8.0 parts, 8.5 parts, 9.0 parts, 9.5 parts or 10.0 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] In some optional examples, the reaction time after adding product A is 4-6h, for example, it can be 4.0h, 4.2h, 4.4h, 4.6h, 4.8h, 5.0h, 5.2h, 5.4h, 5.6h, 5.8h or 6.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] In some optional instances, the fourth temperature is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In some optional examples, the drying time at the fourth temperature is 8-10h, for example, it can be 8.0h, 8.2h, 8.4h, 8.6h, 8.8h, 9.0h, 9.2h, 9.4h, 9.6h, 9.8h or 10.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] As a preferred technical solution of the present invention, in step S4, the mass proportion of the alkaline lignin is 20-30 parts, for example, it can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts or 30 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In some optional examples, the mass fraction of the N,N-dimethylformamide is 400-450 parts, for example, it can be 400 parts, 405 parts, 410 parts, 415 parts, 420 parts, 425 parts, 430 parts, 435 parts, 440 parts, 445 parts or 450 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In some optional examples, the second stirring speed is 200-300 rpm, for example, it can be 200 rpm, 210 rpm, 220 rpm, 230 rpm, 240 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm or 300 rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] In some optional examples, the stirring time of the second stirring speed is 20-30 min, for example, it can be 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] In some optional examples, the mass parts of pyridine are 40-50 parts, for example, it can be 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts or 50 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] In some optional examples, the stirring time after adding pyridine is 10-20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In some optional examples, the mass parts of the hexachlorocyclotriphosphazene are 15-25 parts, for example, it can be 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts or 25 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] In some optional examples, the mass fraction of triphenyl phosphate is 10-15 parts, for example, it can be 10.0 parts, 10.5 parts, 11.0 parts, 11.5 parts, 12.0 parts, 12.5 parts, 13.0 parts, 13.5 parts, 14.0 parts, 14.5 parts or 15.0 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] In some optional examples, the mass parts of N,N-dimethylformamide used to dissolve hexachlorocyclotriphosphazene and triphenyl phosphate are 60-80 parts, for example, it can be 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 76 parts, 78 parts or 80 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In some optional examples, the mass parts of the metaphosphoric acid are 10-15 parts, for example, it can be 10.0 parts, 10.5 parts, 11.0 parts, 11.5 parts, 12.0 parts, 12.5 parts, 13.0 parts, 13.5 parts, 14.0 parts, 14.5 parts or 15.0 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] In some optional examples, the mass proportion of the melamine cyanurate is 5-10 parts, for example, it can be 5.0 parts, 5.5 parts, 6.0 parts, 6.5 parts, 7.0 parts, 7.5 parts, 8.0 parts, 8.5 parts, 9.0 parts, 9.5 parts or 10.0 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] In some optional examples, the mass proportion of titanium dioxide is 3-5 parts, for example, it can be 3.0 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4.0 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts or 5.0 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] In some optional instances, the fourth temperature is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] In some optional examples, the second stirring speed is 200-300 rpm, for example, it can be 200 rpm, 210 rpm, 220 rpm, 230 rpm, 240 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm or 300 rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] In some optional examples, the stirring reaction time at the fourth temperature is 6-8h, for example, it can be 6.0h, 6.2h, 6.4h, 6.6h, 6.8h, 7.0h, 7.2h, 7.4h, 7.6h, 7.8h or 8.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] In some optional instances, the fifth temperature is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In some optional examples, the drying time at the fifth temperature is 12-14h, for example, it can be 12.0h, 12.2h, 12.4h, 12.6h, 12.8h, 13.0h, 13.2h, 13.4h, 13.6h, 13.8h or 14.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] As a preferred technical solution of the present invention, in step S5, the mass proportion of the Mg(OH)2 flame retardant is 20-30 parts, for example, it can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts or 30 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] In some optional examples, the mass fraction of the ethylene-vinyl acetate copolymer is 70-80 parts, for example, it can be 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts or 80 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] In some optional examples, the mass fraction of the vinyl silane is 2-3 parts, for example, it can be 2.0 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts or 3.0 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In some optional examples, the mass proportion of the zinc stearate is 1-2 parts, for example, it can be 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts or 2.0 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In some optional instances, the sixth temperature is 160-180°C, for example, it can be 160°C, 162°C, 164°C, 166°C, 168°C, 170°C, 172°C, 174°C, 176°C, 178°C or 180°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] In some optional instances, the screw speed of the insulating layer material is 100-150rpm, for example, it can be 100rpm, 105rpm, 110rpm, 115rpm, 120rpm, 125rpm, 130rpm, 135rpm, 140rpm, 145rpm or 150rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] In some optional instances, the mixing time of the insulating layer material is 20-30 min, for example, it can be 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] In some optional examples, the mass proportion of the flame retardant lignin is 15-25 parts, for example, it can be 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts or 25 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] In some optional examples, the mass proportion of the flame retardant lignin is 15-25 parts, for example, it can be 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts or 25 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] In some optional examples, the mass proportion of the low-density polyethylene is 75-85 parts, for example, it can be 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts, 84 parts or 85 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0061] In some optional examples, the weight percentage of the antioxidant 1010 is 2-3 parts, for example, it can be 2.0 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts or 3.0 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] In some optional examples, the mass fraction of UV-329 is 1-2 parts, for example, it can be 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts or 2.0 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] In some optional examples, the mass proportion of the zinc stearate is 1-2 parts, for example, it can be 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts or 2.0 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] In some optional instances, the seventh temperature is 140-160°C, for example, it can be 140°C, 142°C, 144°C, 146°C, 148°C, 150°C, 152°C, 154°C, 156°C, 158°C or 160°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] In some optional instances, the screw speed of the sheath layer material is 100-150rpm, for example, it can be 100rpm, 105rpm, 110rpm, 115rpm, 120rpm, 125rpm, 130rpm, 135rpm, 140rpm, 145rpm or 150rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] In some optional instances, the mixing time of the sheath layer material is 20-30 min, for example, it can be 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] In a second aspect, the present invention provides a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system obtained by the preparation method described in the first aspect.

[0068] In a third aspect, the present invention provides a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system.

[0069] Compared with the prior art, the present invention has the following beneficial effects: (1) The modified Mg(OH)2 decomposes at high temperature to release water vapor, absorbs a large amount of heat, and significantly reduces the surface temperature of the material. At the same time, the silicate coated on the surface forms a dense protective layer at high temperature, effectively isolating oxygen and heat and inhibiting the spread of flames. (2) The introduction of flame-retardant lignin containing phosphorus-nitrogen structure, the phosphoric acid derivatives generated by the decomposition of hexachlorocyclotriphosphazene at high temperature can catalyze the carbonization of the material. At the same time, the gas released by the decomposition of nitride has a diluting effect on the combustion zone. The synergistic effect of this chemical reaction effectively interrupts the combustion chain reaction. (3) The flame-retardant lignin introduces phosphorus content through phosphating reaction. Combined with the catalytic effect of titanium dioxide, it quickly carbonizes at high temperature to form a dense carbon layer, which not only insulates heat and oxygen but also blocks the release channel of volatile organic compounds, reducing smoke generation from the source. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 A flow chart of a method for preparing a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system provided in Examples 1-6 of the present invention; Figure 2 This is the SEM image of the Mg(OH)2 flame retardant prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0071] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0072] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products, and their brands, specifications and manufacturer information are as follows: N2, purity ≥99%, Suzhou Chengan Gas Products Co., Ltd.; 2,5-Dihydroxybenzoic acid, purity ≥99%, Shanghai Sanmei Chemical Co., Ltd.; Dimethyl sulfoxide, purity ≥99%, Zhuzhou Hansen Chemical Co., Ltd.; N,N'-Dicyclohexylcarbodiimide, purity ≥99%, Zibo Tiantangshan Chemical Co., Ltd.; N-hydroxysuccinimide, purity ≥99%, Hubei Hongfuda Biotechnology Co., Ltd.; Mg(OH)2, purity ≥99%, Weifang Haililong Magnesium Industry Co., Ltd.; Hexadecyltrimethylammonium bromide, purity ≥98%, Shandong Xirui Chemical Co., Ltd.; Ethanol, purity ≥99%, Yonghua Chemical Co., Ltd.; Sodium hydroxide, purity ≥99%, Tianjin Chengyuan Chemical Co., Ltd.; Tetraethyl orthosilicate, purity ≥99%, Shanghai Aladdin Biochemical Technology Co., Ltd.; Triethylamine, purity ≥99%, Shanghai Aladdin Biochemical Technology Co., Ltd.; Alkaline lignin, purity ≥99%, Shanghai Aladdin Biochemical Technology Co., Ltd.; N,N-dimethylformamide, purity ≥99%, Shandong Aowei Chemical Co., Ltd.; Pyridine, purity ≥99%, Shanghai Aladdin Biochemical Technology Co., Ltd.; Hexachlorocyclotriphosphazene, purity ≥99%, Shandong Zeshi New Materials Technology Co., Ltd.; Triphenyl phosphate, purity ≥99%, Zhangjiagang Yarui Chemical Co., Ltd.; Melamine cyanurate, purity ≥99%, Zhejiang Xusen Flame Retardant Co., Ltd.; Titanium dioxide, purity ≥99%, Henan Longxing Titanium Technology Co., Ltd.; Ethylene-vinyl acetate copolymer, purity ≥99%, Wenzhou Huate Hot Melt Adhesive Co., Ltd.; Vinyl silane, purity ≥99%, Shandong Sike New Materials Co., Ltd.; Zinc stearate, free fatty acid (calculated as stearic acid) ≤ 0.8%, Zanyu Technology Group Co., Ltd.; Low-density polyethylene, purity ≥99%, ExxonMobil Chemical; Antioxidant 1010, purity ≥99%, Tianjin Lianlong New Materials Co., Ltd.; UV-329, purity ≥99%, Nanjing Milan Chemical Co., Ltd.; Other raw materials can be purchased from the market.

[0073] Example 1 This embodiment provides a method for preparing a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system. Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, under N2 atmosphere, 7.3 parts of 2,5-dihydroxybenzoic acid were dispersed in 112 parts of dimethyl sulfoxide and mixed evenly, and then 8.6 parts of N,N'-dicyclohexylcarbodiimide and 5.1 parts of N-hydroxysuccinimide were added, and stirred at 330 rpm for 2.6 hours, and the temperature was raised to 54°C for full reaction for 4.3 hours. After the reaction was completed, the mixture was washed and distilled to obtain product A; Step S2, adding 87 parts of Mg(OH)2 and 3.8 parts of hexadecyltrimethylammonium bromide to 430 parts of ethanol aqueous solution, heating to 44°C, adding 12.3wt.% sodium hydroxide solution to adjust the pH to 10, adding 29 parts of tetraethyl orthosilicate, reacting at 44°C for 4.2h, washing and filtering after the reaction, and vacuum drying at 108°C for 9.1h to obtain modified Mg(OH)2; Step S3, dispersing 84 parts of modified Mg(OH)2 and 1.6 parts of triethylamine in 209 parts of dimethyl sulfoxide, heating to 46°C, adding 7.2 parts of product A and reacting for 4.6 hours, cooling to room temperature after the reaction, washing with anhydrous ethanol, and drying at 83°C for 8.7 hours to obtain Mg(OH)2 flame retardant; Step S4, under N2 atmosphere, 23 parts of alkaline lignin were dissolved in 410 parts of N, N-dimethylformamide, and the mixture was stirred at 230 rpm for 23 min, 43 parts of pyridine were added, and the mixture was stirred for 14 min to obtain a mixed solution, 19 parts of hexachlorocyclotriphosphazene and 13 parts of triphenyl phosphate were dispersed in 68 parts of N, N-dimethylformamide, respectively, and the mixture was added to the mixed solution after dispersion, and then 11.6 parts of metaphosphoric acid, 7.1 parts of melamine cyanurate and 4.2 g of titanium dioxide were added, the mixture was heated to 86°C, and the mixture was stirred at 230 rpm for 6.8 h. After the reaction was completed, the mixture was filtered and washed, and the mixture was fully dried at 63°C for 13.4 h to obtain flame retardant lignin; Step S5, 21 parts of Mg(OH)2 flame retardant, 74 parts of ethylene-vinyl acetate copolymer, 2.2 parts of vinyl silane and 1.6 parts of zinc stearate are mixed in proportion, put into a twin-screw extruder, melt mixed at 168°C, the screw speed is 130rpm, and the mixing time is 22min to obtain an insulating layer material; 17 parts of flame-retardant lignin, 79 parts of low-density polyethylene, 2.4 parts of antioxidant 1010, 1.5 parts of UV-329 and 1.3 parts of zinc stearate are put into a second twin-screw extruder, melt mixed at 146°C, the screw speed is 120rpm, and the mixing time is 22min to obtain a sheath layer material, the insulating layer material and the sheath layer material are uniformly coated on the surface of the battery core in turn, and then the two coated cables are mechanically twisted to obtain a high temperature resistant, low smoke, halogen-free, flame-retardant twisted pair cable for a building security system.

[0074] Figure 2 This is the SEM image of the Mg(OH)2 flame retardant prepared in this example.

[0075] Example 2 This embodiment provides a method for preparing a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system. Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, under N2 atmosphere, 5.9 parts of 2,5-dihydroxybenzoic acid were dispersed in 104 parts of dimethyl sulfoxide and mixed evenly, and then 7.3 parts of N,N'-dicyclohexylcarbodiimide and 4.3 parts of N-hydroxysuccinimide were added, and stirred at 310 rpm for 2.2 hours, and the temperature was raised to 52°C for full reaction for 4.1 hours. After the reaction was completed, the mixture was washed and distilled to obtain product A; Step S2, adding 82 parts of Mg(OH)2 and 2.5 parts of hexadecyltrimethylammonium bromide to 410 parts of ethanol aqueous solution, heating to 41°C, adding 11.6wt.% sodium hydroxide solution to adjust the pH to 10, adding 26 parts of tetraethyl orthosilicate, reacting at 41°C for 4.5h, washing and filtering after the reaction, and vacuum drying at 103°C for 9.5h to obtain modified Mg(OH)2; Step S3, dispersing 87 parts of modified Mg(OH)2 and 1.3 parts of triethylamine in 213 parts of dimethyl sulfoxide, heating to 42°C, adding 6.1 parts of product A and reacting for 4.5 hours, cooling to room temperature after the reaction, washing with anhydrous ethanol, and drying at 86°C for 8.9 hours to obtain Mg(OH)2 flame retardant; Step S4, under N2 atmosphere, 25 parts of alkaline lignin were dissolved in 420 parts of N, N-dimethylformamide, and stirred continuously at 250 rpm for 26 min, 42 parts of pyridine were added and stirred continuously for 12 min to obtain a mixed solution, 17 parts of hexachlorocyclotriphosphazene and 16 parts of triphenyl phosphate were dispersed in 64 parts of N, N-dimethylformamide, and added to the mixed solution after dispersion, and then 10.6 parts of metaphosphoric acid, 6.1 parts of melamine cyanurate and 3.2 g of titanium dioxide were added, the temperature was raised to 82°C, and the reaction was stirred continuously at 250 rpm for 6.4 h. After the reaction was completed, the mixture was filtered and washed, and the mixture was placed at 66°C for 12.6 h to obtain flame retardant lignin; Step S5, 23 parts of Mg(OH)2 flame retardant, 76 parts of ethylene-vinyl acetate copolymer, 2.5 parts of vinyl silane and 1.2 parts of zinc stearate are mixed in proportion, put into a twin-screw extruder, melt mixed at 164°C, the screw speed is 110rpm, and the mixing time is 26min to obtain an insulating layer material; 19 parts of flame-retardant lignin, 77 parts of low-density polyethylene, 2.2 parts of antioxidant 1010, 1.3 parts of UV-329 and 1.5 parts of zinc stearate are put into a second twin-screw extruder, melt mixed at 151°C, the screw speed is 130rpm, and the mixing time is 24min to obtain a sheath layer material, the insulating layer material and the sheath layer material are uniformly coated on the surface of the battery core in turn, and then the two coated cables are mechanically twisted to obtain a high temperature resistant, low smoke, halogen-free, flame-retardant twisted pair cable for a building security system.

[0076] Example 3 This embodiment provides a method for preparing a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system. Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, under N2 atmosphere, 6.2 parts of 2,5-dihydroxybenzoic acid are dispersed in 108 parts of dimethyl sulfoxide and mixed evenly, and then 7.6 parts of N,N'-dicyclohexylcarbodiimide and 4.7 parts of N-hydroxysuccinimide are added, and stirred at 370 rpm for 2.4 hours, and the temperature is raised to 56°C for full reaction for 4.6 hours. After the reaction is completed, the product A is washed and distilled to obtain the product; Step S2, adding 88 parts of Mg(OH)2 and 2.9 parts of hexadecyltrimethylammonium bromide to 430 parts of ethanol aqueous solution, heating to 46°C, adding 13.4wt.% sodium hydroxide solution to adjust the pH to 10, adding 29 parts of tetraethyl orthosilicate, reacting at 46°C for 4.3h, washing and filtering after the reaction, and vacuum drying at 108°C for 8.3h to obtain modified Mg(OH)2; Step S3, dispersing 82 parts of modified Mg(OH)2 and 1.3 parts of triethylamine in 208 parts of dimethyl sulfoxide, heating to 44°C, adding 5.7 parts of product A and reacting for 4.8 hours, cooling to room temperature after the reaction, washing with anhydrous ethanol, and drying at 82°C for 8.3 hours to obtain Mg(OH)2 flame retardant; Step S4, under N2 atmosphere, 22 parts of alkaline lignin were dissolved in 410 parts of N, N-dimethylformamide, and the mixture was stirred at 260 rpm for 22 min, 48 parts of pyridine were added, and stirring was continued for 14 min to obtain a mixed solution, 19 parts of hexachlorocyclotriphosphazene and 12 parts of triphenyl phosphate were dispersed in 73 parts of N, N-dimethylformamide, respectively, and the dispersed parts were added to the mixed solution, and then 11.7 parts of metaphosphoric acid, 6.8 parts of melamine cyanurate and 3.7 g of titanium dioxide were added, the temperature was raised to 85°C, and the mixture was stirred at 260 rpm for 7.2 h. After the reaction was completed, the mixture was filtered and washed, and the mixture was fully dried at 63°C for 12.9 h to obtain flame retardant lignin; Step S5, 25 parts of Mg(OH)2 flame retardant, 73 parts of ethylene-vinyl acetate copolymer, 2.2 parts of vinyl silane and 1.4 parts of zinc stearate are mixed in proportion, put into a twin-screw extruder, melt-mixed at 168°C, the screw speed is 130rpm, and the mixing time is 20min to obtain an insulating layer material; 18 parts of flame-retardant lignin, 81 parts of low-density polyethylene, 2.6 parts of antioxidant 1010, 1.5 parts of UV-329 and 1.3 parts of zinc stearate are put into a second twin-screw extruder, melt-mixed at 154°C, the screw speed is 110rpm, and the mixing time is 27min to obtain a sheath layer material, the insulating layer material and the sheath layer material are uniformly coated on the surface of the battery core in turn, and then the two coated cables are mechanically twisted to obtain a high temperature resistant, low smoke, halogen-free, flame-retardant twisted pair cable for a building security system.

[0077] Example 4 This embodiment provides a method for preparing a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system. Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, under N2 atmosphere, 8.1 parts of 2,5-dihydroxybenzoic acid are dispersed in 118 parts of dimethyl sulfoxide and mixed evenly, and then 8.5 parts of N,N'-dicyclohexylcarbodiimide and 5.3 parts of N-hydroxysuccinimide are added, and stirred at 340 rpm for 2.8 hours, and the temperature is raised to 52°C for full reaction for 4.8 hours. After the reaction is completed, the product A is washed and distilled to obtain the product; Step S2, adding 93 parts of Mg(OH)2 and 3.7 parts of hexadecyltrimethylammonium bromide to 420 parts of ethanol aqueous solution, heating to 49°C, adding 12.6wt.% sodium hydroxide solution to adjust the pH to 10, adding 32 parts of tetraethyl orthosilicate, reacting at 49°C for 4.8h, washing and filtering after the reaction, and vacuum drying at 113°C for 9.4h to obtain modified Mg(OH)2; Step S3, dispersing 94 parts of modified Mg(OH)2 and 1.7 parts of triethylamine in 216 parts of dimethyl sulfoxide, heating to 47°C, adding 8.6 parts of product A and reacting for 5.1 hours, cooling to room temperature after the reaction, washing with anhydrous ethanol, and drying at 85°C for 9.2 hours to obtain Mg(OH)2 flame retardant; Step S4, under N2 atmosphere, 24 parts of alkaline lignin were dissolved in 420 parts of N, N-dimethylformamide, and the mixture was stirred at 210 rpm for 27 min, 43 parts of pyridine were added, and stirring was continued for 16 min to obtain a mixed solution, 22 parts of hexachlorocyclotriphosphazene and 16 parts of triphenyl phosphate were dispersed in 77 parts of N, N-dimethylformamide, respectively, and the dispersed parts were added to the mixed solution, and then 13.4 parts of metaphosphoric acid, 7.6 parts of melamine cyanurate and 4.3 g of titanium dioxide were added, the temperature was raised to 88°C, and the mixture was stirred at 210 rpm for 7.6 h. After the reaction was completed, the mixture was filtered and washed, and the mixture was fully dried at 68°C for 13.3 h to obtain flame retardant lignin; Step S5, 28 parts of Mg(OH)2 flame retardant, 72 parts of ethylene-vinyl acetate copolymer, 2.5 parts of vinyl silane and 1.8 parts of zinc stearate are mixed in proportion, put into a twin-screw extruder, melt mixed at 174°C, the screw speed is 140rpm, and the mixing time is 23min to obtain an insulating layer material; 20 parts of flame-retardant lignin, 80 parts of low-density polyethylene, 2.2 parts of antioxidant 1010, 1.6 parts of UV-329 and 1.8 parts of zinc stearate are put into a second twin-screw extruder, melt mixed at 150°C, the screw speed is 130rpm, and the mixing time is 26min to obtain a sheath layer material, the insulating layer material and the sheath layer material are uniformly coated on the surface of the battery core in turn, and then the two coated cables are mechanically twisted to obtain a high temperature resistant, low smoke, halogen-free, flame-retardant twisted pair cable for a building security system.

[0078] Example 5 This embodiment provides a method for preparing a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system. Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, under N2 atmosphere, 7.0 parts of 2,5-dihydroxybenzoic acid are dispersed in 104 parts of dimethyl sulfoxide and mixed evenly, and then 8.1 parts of N,N'-dicyclohexylcarbodiimide and 5.2 parts of N-hydroxysuccinimide are added, and stirred at 370 rpm for 2.3 hours, and the temperature is raised to 56°C for full reaction for 4.3 hours. After the reaction is completed, the product A is washed and distilled to obtain the product; Step S2, adding 90 parts of Mg(OH)2 and 4.1 parts of hexadecyltrimethylammonium bromide to 470 parts of ethanol aqueous solution, heating to 46°C, adding 13.0wt.% sodium hydroxide solution to adjust the pH to 10, adding 31 parts of tetraethyl orthosilicate, reacting at 46°C for 4.4h, washing and filtering after the reaction, and vacuum drying at 110°C for 9.2h to obtain modified Mg(OH)2; Step S3, dispersing 88 parts of modified Mg(OH)2 and 1.3 parts of triethylamine in 211 parts of dimethyl sulfoxide, heating to 45°C, adding 8.3 parts of product A and reacting for 5.4 hours, cooling to room temperature after the reaction, washing with anhydrous ethanol, and drying at 83°C for 9.4 hours to obtain Mg(OH)2 flame retardant; Step S4, under N2 atmosphere, 26 parts of alkaline lignin were dissolved in 440 parts of N, N-dimethylformamide, and stirred continuously at 280 rpm for 22 min, 41 parts of pyridine were added and stirred continuously for 13 min to obtain a mixed solution, 20 parts of hexachlorocyclotriphosphazene and 13 parts of triphenyl phosphate were dispersed in 71 parts of N, N-dimethylformamide, respectively, and added to the mixed solution after dispersion, and then 14.3 parts of metaphosphoric acid, 7.2 parts of melamine cyanurate and 3.2 g of titanium dioxide were added, the temperature was raised to 83°C, and the reaction was stirred continuously at 280 rpm for 7.2 h. After the reaction was completed, the mixture was filtered and washed, and the mixture was placed at 64°C and fully dried for 12.6 h to obtain flame retardant lignin; Step S5, 22 parts of Mg(OH)2 flame retardant, 74 parts of ethylene-vinyl acetate copolymer, 2.6 parts of vinyl silane and 1.3 parts of zinc stearate are mixed in proportion, put into a twin-screw extruder, melt mixed at 170°C, the screw speed is 120rpm, and the mixing time is 28min to obtain an insulating layer material; 21 parts of flame-retardant lignin, 83 parts of low-density polyethylene, 2.5 parts of antioxidant 1010, 1.3 parts of UV-329 and 1.6 parts of zinc stearate are put into a second twin-screw extruder, melt mixed at 155°C, the screw speed is 110rpm, and the mixing time is 24min to obtain a sheath layer material, the insulating layer material and the sheath layer material are uniformly coated on the surface of the battery core in turn, and then the two coated cables are mechanically twisted to obtain a high temperature resistant, low smoke, halogen-free, flame-retardant twisted pair cable for a building security system.

[0079] Example 6 This embodiment provides a method for preparing a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system. Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, under N2 atmosphere, 6.5 parts of 2,5-dihydroxybenzoic acid are dispersed in 108 parts of dimethyl sulfoxide and mixed evenly, and then 8.3 parts of N,N'-dicyclohexylcarbodiimide and 5.0 parts of N-hydroxysuccinimide are added, and stirred at 320 rpm for 2.6 hours, and the temperature is raised to 58°C for full reaction for 4.6 hours. After the reaction is completed, the product A is washed and distilled to obtain the product; Step S2, adding 95 parts of Mg(OH)2 and 3.7 parts of hexadecyltrimethylammonium bromide to 450 parts of ethanol aqueous solution, heating to 48°C, adding 13.9wt.% sodium hydroxide solution to adjust the pH to 10, adding 33 parts of tetraethyl orthosilicate, reacting at 48°C for 4.2h, washing and filtering after the reaction, and vacuum drying at 114°C for 8.6h to obtain modified Mg(OH)2; Step S3, dispersing 91 parts of modified Mg(OH)2 and 1.5 parts of triethylamine in 216 parts of dimethyl sulfoxide, heating to 47°C, adding 8.8 parts of product A and fully reacting for 4.7 hours, cooling to room temperature after the reaction, washing with anhydrous ethanol, and fully drying at 86°C for 9.2 hours to obtain Mg(OH)2 flame retardant; Step S4, under N2 atmosphere, 22 parts of alkaline lignin were dissolved in 430 parts of N, N-dimethylformamide, and stirred continuously at 240 rpm for 26 min, 45 parts of pyridine were added and stirred continuously for 16 min to obtain a mixed solution, 19 parts of hexachlorocyclotriphosphazene and 16 parts of triphenyl phosphate were dispersed in 75 parts of N, N-dimethylformamide, respectively, and added to the mixed solution after dispersion, and then 12.3 parts of metaphosphoric acid, 8.2 parts of melamine cyanurate and 4.1 g of titanium dioxide were added, the temperature was raised to 85°C, and the reaction was stirred continuously at 240 rpm for 7.5 h. After the reaction was completed, the mixture was filtered and washed, and the mixture was placed at 66°C and fully dried for 12.9 h to obtain flame retardant lignin; Step S5, 24 parts of Mg(OH)2 flame retardant, 77 parts of ethylene-vinyl acetate copolymer, 2.2 parts of vinyl silane and 1.8 parts of zinc stearate are mixed in proportion, put into a twin-screw extruder, melt mixed at 174°C, the screw speed is 150rpm, and the mixing time is 23min to obtain an insulating layer material; 23 parts of flame-retardant lignin, 81 parts of low-density polyethylene, 2.6 parts of antioxidant 1010, 1.4 parts of UV-329 and 1.7 parts of zinc stearate are put into a second twin-screw extruder, melt mixed at 152°C, the screw speed is 120rpm, and the mixing time is 27min to obtain a sheath layer material, the insulating layer material and the sheath layer material are uniformly coated on the surface of the battery core in turn, and then the two coated cables are mechanically twisted to obtain a high temperature resistant, low smoke, halogen-free, flame-retardant twisted pair cable for a building security system.

[0080] Comparative Example 1 This comparative example provides a method for preparing a high-temperature resistant, low-smoke, halogen-free, flame-retardant twisted-pair cable for a building security system. The difference between the comparative example and Example 1 is that the mass portion of tetraethyl orthosilicate in step S2 is adjusted to 39 parts, and the mass portion of tetraethyl orthosilicate is increased by 10 parts compared with Example 1. The increased mass portions are deducted from Mg(OH)2, hexadecyltrimethylammonium bromide and ethanol aqueous solution in equal proportions, and the other process parameters and operating conditions are exactly the same as those in Example 1.

[0081] Comparative Example 2 This comparative example provides a method for preparing a high-temperature resistant, low-smoke, halogen-free, flame-retardant twisted-pair cable for a building security system. The difference between the comparative example and Example 1 is that the mass portion of tetraethyl orthosilicate in step S2 is adjusted to 19 parts, and the mass portion of tetraethyl orthosilicate is reduced by 10 parts compared with Example 1. The reduced mass portion is added to Mg(OH)2, hexadecyltrimethylammonium bromide and ethanol aqueous solution in equal proportion, and the other process parameters and operating conditions are exactly the same as those in Example 1.

[0082] Comparative Example 3 This comparative example provides a method for preparing a high-temperature resistant, low-smoke, halogen-free, flame-retardant twisted-pair cable for a building security system. The difference between the comparative example and Example 1 is that the mass portion of hexachlorocyclotriphosphazene in step S4 is adjusted to 27 parts, and the mass portion of tetraethyl orthosilicate is increased by 8 parts compared with Example 1, and the increased mass portion is deducted from the proportion of alkaline lignin, N,N-dimethylformamide, pyridine, triphenyl phosphate, metaphosphoric acid, melamine cyanurate and titanium dioxide. The other process parameters and operating conditions are exactly the same as those in Example 1.

[0083] Comparative Example 4 This comparative example provides a method for preparing a high-temperature resistant, low-smoke, halogen-free, flame-retardant twisted-pair cable for a building security system. The difference between the comparative example and Example 1 is that the mass portion of hexachlorocyclotriphosphazene in step S4 is adjusted to 11 parts, and the mass portion of tetraethyl orthosilicate is reduced by 8 parts compared with Example 1. The reduced mass portion is added to alkaline lignin, N,N-dimethylformamide, pyridine, triphenyl phosphate, metaphosphoric acid, melamine cyanurate and titanium dioxide in equal proportions, and the other process parameters and operating conditions are exactly the same as those in Example 1.

[0084] The limiting oxygen index of the materials prepared in Examples 1-6 and Comparative Examples 1-4 was tested according to the national standard GB / T 2406.2-2009; the flame retardant properties of the materials prepared in Examples 1-6 and Comparative Examples 1-4 were tested according to GB / T 2408-2021; the maximum smoke density of the materials prepared in Examples 1-6 and Comparative Examples 1-4 was tested according to the national standard GB / T 32129-2015. The test results are shown in Table 1.

[0085] Table 1 Test results of high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cables for building security systems in Examples 1-6 and Comparative Examples 1-4 It can be seen from the data in the table that the limiting oxygen index and flame retardant grade of comparative example 1 are lower than those of example 1, and the maximum smoke density (flameless) is higher than that of example 1; the limiting oxygen index and flame retardant grade of comparative example 2 are lower than those of example 1, and the maximum smoke density (flameless) is higher than that of example 1. This is because the excessive tetraethyl orthosilicate in comparative example 1 may form too much silicate layer on the surface of Mg(OH)2, resulting in the weakening of the decomposition endothermic effect and water release ability of the material, thereby reducing the flame retardant performance of the material at high temperature, and water vapor plays a role in diluting combustible gas in a fire. If the release is insufficient, the smoke suppression effect will be weakened. In comparative example 2, the tetraethyl orthosilicate is insufficient, resulting in incomplete coverage of silicate, which cannot fully protect the surface of Mg(OH)2, reduce the fire resistance of Mg(OH)2, and reduce the flame retardant performance of the material.

[0086] The limiting oxygen index and flame retardant grade of comparative example 3 are lower than those of example 1, and the maximum smoke density (flameless) is higher than that of example 1; the limiting oxygen index and flame retardant grade of comparative example 4 are lower than those of example 1, and the maximum smoke density (flameless) is higher than that of example 1. This is because the chlorine atoms of hexachlorocyclotriphosphazene in comparative example 3 will lead to excessive nucleophilic substitution reaction under excessive conditions, not only will they replace the phenolic hydroxyl groups of lignin, but the excess hexachlorocyclotriphosphazene may also trigger multi-step chlorination reaction, resulting in chlorine substitution or ring-opening reaction of aromatic rings, weakening its carbonization ability at high temperature, and at the same time, the excess hexachlorocyclotriphosphazene may decompose during combustion, generating toxic fumes such as hydrogen chloride, which increases the generation of smoke. In comparative example 4, hexachlorocyclotriphosphazene is insufficient, the generation of new chemical bonds -P=N is insufficient, the chemical stability and thermal stability of the material are insufficient, and the free radicals in the flame cannot be effectively captured to inhibit the combustion chain reaction, resulting in a decrease in flame retardant properties.

[0087] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system, characterized in that: The preparation method is: Step S1, under N2 atmosphere, 2,5-dihydroxybenzoic acid is dispersed in dimethyl sulfoxide and mixed evenly, then N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide are added, and the mixture is continuously stirred, and the temperature is raised to a first temperature for sufficient reaction, and after the reaction is completed, the mixture is washed and distilled to obtain product A; Step S2, adding Mg(OH)2 and an emulsifier to an ethanol aqueous solution, heating to a second temperature, adding a sodium hydroxide solution to adjust the pH to 10, adding tetraethyl orthosilicate, and fully reacting at the second temperature, washing and filtering after the reaction is completed, and vacuum drying at a third temperature to obtain modified Mg(OH)2; Step S3, dispersing modified Mg(OH)2 and triethylamine in dimethyl sulfoxide, heating to the second temperature, adding product A to fully react, cooling to room temperature after the reaction, washing with anhydrous ethanol, and fully drying at a fourth temperature to obtain a Mg(OH)2 flame retardant; Step S4, under N2 atmosphere, dissolving alkaline lignin in N,N-dimethylformamide with continuous stirring, adding pyridine and continuing stirring to obtain a mixed solution, dispersing hexachlorocyclotriphosphazene and triphenyl phosphate in N,N-dimethylformamide respectively, adding the dispersed solutions to the mixed solution, adding metaphosphoric acid, melamine cyanurate and titanium dioxide, heating to a fourth temperature and continuing stirring to react, filtering and washing after the reaction is completed, and placing at a fifth temperature to be fully dried to obtain flame retardant lignin; Step S5, mixing Mg(OH)2 flame retardant, ethylene-vinyl acetate copolymer, vinyl silane and zinc stearate in proportion, putting them into a twin-screw extruder, and melt mixing them at a sixth temperature to obtain an insulating layer material; putting flame-retardant lignin, low-density polyethylene, antioxidant 1010, UV-329 and zinc stearate into a second twin-screw extruder, and melt mixing them at a seventh temperature to obtain a sheath layer material, and uniformly coating the insulating layer material and the sheath layer material on the surface of the battery core in turn, and then mechanically twisting the two coated cables to obtain a high temperature resistant, low smoke, halogen-free, flame-retardant twisted pair cable for a building security system.

2. The method for preparing a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system according to claim 1, characterized in that: In step S1, The mass fraction of the 2,5-dihydroxybenzoic acid is 5-10 parts; The mass parts of the dimethyl sulfoxide are 100-120 parts; The mass fraction of the N,N'-dicyclohexylcarbodiimide is 7-9 parts; The mass parts of the N-hydroxysuccinimide are 4-6 parts; The first temperature is 50-60°C; The reaction time at the first temperature is 4-5h.

3. The method for preparing a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system according to claim 1, characterized in that: In step S2, The mass fraction of Mg(OH)2 is 80-100 parts; The emulsifier is hexadecyltrimethylammonium bromide, with a mass fraction of 2-5 parts; The mass parts of the ethanol aqueous solution are 400-500 parts, and the volume ratio of ethanol to deionized water is 3:1; The second temperature is 40-50°C.

4. The method for preparing a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system according to claim 1, characterized in that: In step S2, The mass fraction of the sodium hydroxide solution is 10-15wt.%; The mass fraction of tetraethyl orthosilicate is 25-35 parts; The reaction time after adding tetraethyl orthosilicate is 4-5h; The third temperature is 100-120° C. The vacuum drying time at the third temperature is 8-10 hours.

5. The method for preparing a high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system according to claim 1, characterized in that: In step S3, The mass fraction of the modified Mg(OH)2 is 80-100 parts; The mass fraction of the triethylamine is 1-2 parts; The mass parts of the dimethyl sulfoxide are 200-220 parts; The second temperature is 40-50°C; The mass fraction of the product A is 5-10 parts; The reaction time after adding product A is 4-6h; The fourth temperature is 80-90°C; The drying time at the fourth temperature is 8-10 hours.

6. The method for preparing a high temperature resistant, low smoke, halogen free, flame retardant twisted pair cable for a building security system according to claim 1, characterized in that: In step S4, The mass fraction of the alkaline lignin is 20-30 parts; The mass parts of the N,N-dimethylformamide are 400-450 parts; The mass parts of the pyridine are 40-50 parts; The stirring time after adding pyridine is 10-20min; The mass parts of the hexachlorocyclotriphosphazene are 15-25 parts; The mass fraction of triphenyl phosphate is 10-15 parts; The mass proportion of N,N-dimethylformamide used for dissolving hexachlorocyclotriphosphazene and triphenyl phosphate is 60-80 parts.

7. The method for preparing a high temperature resistant, low smoke, halogen free, flame retardant twisted pair cable for a building security system according to claim 1, characterized in that: In step S4, The mass parts of the metaphosphoric acid are 10-15 parts; The mass parts of the melamine cyanurate are 5-10 parts; The mass fraction of the titanium dioxide is 3-5 parts; The fourth temperature is 80-90°C; The stirring reaction time at the fourth temperature is 6-8h; The fifth temperature is 60-70°C; The drying time at the fifth temperature is 12-14 hours.

8. The method for preparing a high temperature resistant, low smoke, halogen free, flame retardant twisted pair cable for a building security system according to claim 1, characterized in that: In step S5, The components of the insulating layer material are as follows: 20-30 parts of Mg(OH)2 flame retardant, 70-80 parts of ethylene-vinyl acetate copolymer, 2-3 parts of vinyl silane, and 1-2 parts of zinc stearate; The sixth temperature is 160-180°C; The screw speed of the insulating layer material is 100-150rpm, and the mixing time is 20-30min; The components of the sheath layer material are as follows: 15-25 parts of flame retardant lignin, 75-85 parts of low-density polyethylene, 2-3 parts of antioxidant 1010, 1-2 parts of UV-329, and 1-2 parts of zinc stearate; The seventh temperature is 140-160°C; The screw speed of the sheath layer material is 100-150 rpm, and the mixing time is 20-30 min.

9. A high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable for a building security system obtained according to the preparation method according to any one of claims 1 to 8.

10. Application of the high temperature resistant, low smoke, halogen-free, flame retardant twisted pair cable prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The high temperature resistant, low smoke, halogen free and flame retardant twisted pair cable is applied to building security systems.

Citation Information

Patent Citations

  • Method for preparing micro-nanometer magnetic materials by using straight-chain hydrophilic polymer with carboxyl at two ends to coat nanometer magnetic cores and application thereof

    CN102617810A

  • Organic-inorganic hybridized nanometer compound with chain extension-flame retardant synergistic effect, and preparation method and flame retardant polylactic acid thereof

    CN106928490A

  • Photosensitive resin composition, method for manufacturing cured relief pattern, and semiconductor apparatus

    CN107850844A

  • Expansive colloid based on ethylene-vinyl acetate copolymer resin matrix and preparation method thereof

    CN110938251A

  • Hydrophobic flame retardant and preparation method thereof

    CN111154142A

Cited By

  • High-temperature-resistant low-smoke zero halogen flame-retardant twisted-pair cable for building security system, and manufacturing method therefor

    WO2026123700A1